Gut microbial alteration in chronic spontaneous urticaria unresponsive to second generation antihistamines and its correlation with disease characteristics‐ a cross‐sectional case‐control study - Indrashis Podder; David Pesqué; Nerea Carrón; Pedro Iñaki González Torres; Ramon M. Pujol; Ana M. Giménez‐Arnau (Clinical and Translational Allergy)
Abstract Background Gut microbial involvement has been speculated in chronic spontaneous urticaria (CSU). The aim of the study was to compare the gut microbiome composition and diversity in CSU patients uncontrolled with second‐generation antihistamines (sgAHs) and healthy individuals, as well as to explore any association between gut microbiome and disease characteristics. Methods A cross‐sectional case‐control study including 20 CSU patients unresponsive to standard doses of sgAHs, and 15 age‐and‐sex matched healthy controls was conducted. Clinico‐demographic profile, laboratory investigations and stool analysis were conducted in all study participants. 16S RNA gene sequencing and DNA isolation was performed for all stool samples, followed by bioinformatic analysis. Results The CSU patients (mean age 39.5 ± 9.3, M:F 1:4) and healthy controls (mean age 35 ± 13, M:F 1:2) were statistically comparable. The median (IQR) duration of CSU was 42 months (7–81). Concomitant angioedema and concomitant symptomatic dermographism were present in 30% and 20% CSU patients, respectively. At inclusion, 60% patients were receiving add‐on omalizumab, while the remaining 40% were on up‐dosed sgAHs. Stool microbial analysis revealed increased diversity and higher microbial richness in CSU patients compared with healthy individuals. CSU patients showed reduced load of short‐chain fatty acid (SCFA) producing microbiota and increased load of opportunistic pathogens. The Firmicutes/Bacteroides (F/B) ratio was higher in CSU patients. Among CSU patients, higher Bacteroides and reduced Firmicutes count were associated with higher disease activity and poor control; however, there was no link with the type of therapy. Conclusion Gut microbial dysbiosis is seen in CSU and is linked with disease control.